2023
DOI: 10.3390/ijms241210354
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Potential of Natural Chalcones: In Vitro and In Vivo Evidence

Radka Michalkova,
Ladislav Mirossay,
Martin Kello
et al.

Abstract: There is no doubt that significant progress has been made in tumor therapy in the past decades. However, the discovery of new molecules with potential antitumor properties still remains one of the most significant challenges in the field of anticancer therapy. Nature, especially plants, is a rich source of phytochemicals with pleiotropic biological activities. Among a plethora of phytochemicals, chalcones, the bioprecursors of flavonoid and isoflavonoids synthesis in higher plants, have attracted attention due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 352 publications
(433 reference statements)
0
3
0
Order By: Relevance
“…The induction of apoptosis by chalcones, particularly through the activation of caspase-3, is a well-documented phenomenon [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In our study, the data suggested that DDC preferentially activated caspase-3 over caspase-7 in MDA-MB-231 cells, as illustrated in Figure 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The induction of apoptosis by chalcones, particularly through the activation of caspase-3, is a well-documented phenomenon [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In our study, the data suggested that DDC preferentially activated caspase-3 over caspase-7 in MDA-MB-231 cells, as illustrated in Figure 5 .…”
Section: Discussionmentioning
confidence: 99%
“…How ever, only a few of these natural chalcones possess both hydroxy and methoxy groups in their structures (Table 1). One well-known subgroup of these chalcones is called flavoka vains, which were originally identified in Piper methysticum (Kava) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the search for new therapeutics aimed at reducing side effects and the treatment of recurrences, naturally occurring compounds have been of inspiration for their pleiotropic activities [ 6 , 7 , 8 ]. In the last two decades, curcumin [(1E,6E)-1,7-bis (4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione], the most active phytocompound extracted from the dried rhizomes of Curcuma longa L., stands out, as highlighted by the exponential increase in released scientific papers, reviews, and clinical trials.…”
Section: Introductionmentioning
confidence: 99%